Pooling Method for Screening Large Numbers of Escherichia coli for Production of Heat-Stable Enterotoxin, and Its Application in Field Studies - Byers, Patricia A. (1979)
A modified suckling mouse assay was developed for use in field studies whereby five E. coli isolates could be tested as a pool for heat-stable enterotoxin.